Students’ Experience During their Stay at the University Academy: Result from the Exit Survey - Sarmiento, Ardelma V.; Balila, Jolly S.; Ibañez, Mercedes M. (11th International Scholars Conference, 2018)
Effective monitoring and evaluation is deemed necessary to determine whether the school is delivering to the desired results and improve planning and its operations. Thus, this quantitative study aimed to evaluate the strengths and weaknesses of a University Academy (UA) operation. Utilizing an exit survey instrument, data were taken from randomly sampled 100 UA alumni from 2016 and earlier. Results from the descriptive analysis showed that respondents had a very good academic learning experiences, students-faculty interaction and extra and co-curricular activities. Respondents were very satisfied with the administrative and academic support services. Further, it was found that the overall perception was very high, indicating that they had gained a lot from the UA and had quality relationship with the administration, fellow students, faculty and staff. It was also revealed that their relationship with God became stronger. Forty-six percent (46%) strongly recommended the school to friends and relatives. Among the total number of respondents, only 20% had encountered difficult problems at the school, specifically in fulfilling class requirements, participating in class activities and managing time. A difference was evident in the approach students take in learning. Thus, it was recommended that students be given opportunities to engage in selfdirected learning activities and lessons be directed towards students’ holistic growth.